WONG TUWO AS A MODEL OF CONFLICT RESOLUTION IN THE TARIQA QADIRIYAH WA NAQSYABANDIYAH - Masduki Masduki; Imron Rosidi; Toni Hartono (UIN Antasari Banjarmasin, 2022)
This article analyzes a conflict resolution model practiced among the followers of the Tariqa Qadiriyah wa Naqsyabandiyah. This research uses a philosophical and ethnographic method to analyze the social life of the followers of Tariqa Qadiriyah wa Naqsyabandiyah in Riau, Indonesia. Through these methods, this article finds that the Tariqa followers have established a conflict resolution philosophy called the Wong Tuwo. This philosophy appears from the concept of an individual as a peacebuilder that has to live and has character harmoniously, friendly, and ethically among human beings beyond ethnicity, culture, and religion. The